Pengaruh Mekanisme Good Corporate Governance (GCG) dan Profitabilitas Perusahaan Terhadap Peringkat Obligasi (studi empiris pada Perusahaan Manufaktur yang terdaftar di BEI tahun 2014-2015) - Sahhyla, Kunni Fauztina; Sulistyo, Sulistyo; Mustikowati, Rita Indah (Jurnal Riset Mahasiswa Akuntansi, 2018)
This study aims to determine the effect of good corporate governance mechanisms and company profitability on bond ratings. The population used in this study is companies listed on the Indonesia Stock Exchange for the period 2014-2015 and the sample determination method used is purposive judgment sampling. Samples obtained were 32 bond issuing companies. Data analysis techniques used are descriptive analysis, classic assumption test, multiple linear regression test, and hypothesis testing. This study found that simultaneous mechanisms of good corporate governance and corporate profitability affect bond ratings. Partially, this study found that the mechanism of good corporate governance that was proxied by the board of directors (DD), audit committee (KA), company size (UK), board of directors (DK) and profitability that was proxied by Return on Assets affected the bond rating, whereas Managerial ownership (KM), institutional ownership (IC) have no effect on bond ratings.